Comments on "temperature‐extreme precipitation scaling: A two‐way causality?". (17th August 2018) - Bao, Jiawei; Sherwood, Steven C.; Alexander, Lisa V.; Evans, Jason P.
Abstract : Recently, Barbero et al . (2018) examined temperature‐extreme precipitation scaling and argue that the local cooling effect leading to negative apparent scaling in Darwin found by Bao et al . (2017a) was simply a statistical artefact. Barbero et al . (2018) also propose that dew point temperature drives extreme precipitation, and should be used as a scaling variable. Here we address some of their criticisms and further clarify some conclusions. We maintain that scaling analyses via "binning methods" cannot be reliably applied to climate changes due to fundamental problems of misinterpreted causality, and that using dew point temperature does not solve these problems. Abstract : Time series of daily mean temperature from the 20 driest days in 12 temperature bins from 7 days before to 7 days after the events in Darwin from Australian water availability project (Jones et al., 2009). Different colours from darkest blue (coolest) to darkest red (warmest) represent mean evolution of cases in 12 different temperature bins